Progress in interface structure and modification of zinc anode for aqueous batteries. (July 2022) - Qin, Runzhi; Wang, Yuetao; Yao, Lu; Yang, Luyi; Zhao, Qinghe; Ding, Shouxiang; Liu, LeLe; Pan, Feng
Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) are an attractive option for large-scale energy storage. However, the zinc anode's poor cycling performance precludes practical implementation, owing to uncontrolled dendrite growth and rampant side reactions. Recently, the strategy of interface modification on the zinc anode has been widely explored, and numerous coating materials are reported to have a positive impact on the electrochemical performance. To facilitate comprehension, we present an overview of this strategy. The challenges of state-of-the-art zinc anodes are first introduced, and the preparation methods of the coating materials are classified. Then, the structures and fundamental functions of various modifications are summarized. Additionally, the optimization mechanisms focusing on dendrite control, coulombic efficiency elevation, and some technical issues are discussed in detail. Finally, various points of contention and confusion are mentioned, and the perspectives are provided. We anticipate this review will inspire the researchers, and serve as a guide for future development on interface modification of zinc anodes and ZIBs. Graphical Abstract: The critical issues of uncontrolled dendrites and undesirable CE for zinc anode can be effectively settled by interface modifications. The structure, fundamental mechanism, and the optimizations of interface modifications are discussed in this review. ga1 Highlights: The structure and fundamental mechanism of interface modifications are catalogued and summarized. Optimization strategies for dendrite suppression and CE elevation at each electrochemical process are discussed in detail. Controversies & confusions are provided to deppen understanding, and perspective is also proposed for advanced zinc anode.